Industrial waste inventory and integrated waste management scheme for Cavite Economic Zone - Bansuli, Cielo B. (2004)
The Philippines, is one of the developing countries in Asia that has experienced significant industrial growth in recent years and this has coincided with the establishment of the Philippine Economic Zone Authority (PEZA) in 1995, which in turn gave rise the about ninety-six (96) number of industrial estates in the country. Cavite Economic Zone is the largest of he four government-managed industrial estates operated by PEZA. This industrial estate generated 29 percent of the total exports of the Philippines in 2002. However, the industrial estate generates significant amounts of industrial waste and currently there is no centralized waste management program. The Ecological and Solid Waste Management Act (RA 9003) and the Toxic Substances and Hazardous Waste Management Act (RA 6969) of the Philippines require that solid waste and treated hazardous waste is disposed in a landfill while the Clean Air Act (RA 6749) bans the use of incinerators for such waste. Currently, there is no available landfill in the Province of Cavite or in its surrounding area. Also, while there are a number of environmental service providers, the services provided by these companies are inadequate of expensive. The integration of waste management schemes, which is possible in an industrial estate, has the potential to help solve some of the abovementioned problems by ensuring efficient waste management in relatively economic terms. To achieve this, the following specific objectives are to be undertaken: 1. To determine the total quantity and characteristics of the non-hazardous solid waste generated at the industrial estate. 2. To establish a waste flow alternative that will maximize the potential for resource recovery from the waste. 3. To identify the basic components for a centralized waste recovery, treatment and disposal facility. A waste survey was designed in order to obtain data in relation to waste type and volume generated by locators within the industrial estate as reported by locators, garbage collectors and hazardous waste treaters over the three-month period comprising June to August 2001. The waste survey was issued to the different respondents by the administration office of the industrial estate and this ensured a one-hundred percent response rate.
The survey data collected from different respondents were processed and analyzed. This involved the conversion of quantity data to the similar volume unit to enable comparison and most importantly to enable summation of values. It also includes the grouping of waste per type and per industry source. Based on the survey, the total waste emanating from the industrial estate is 10,512 cu.m. Hazardous waste accounted for 86 percent of the total waste generation with a total quantity of 9091 cu.m daily. There are twenty-three items under the hazardous waste classification and 75 percent was in solid form and the rest in liquid form. On the non-hazardous solid waste, there are nine various types with a total volume of 1421 cu.m daily. The inventoried wastes were classified according to its corresponding level in the waste management hierarchy, which was then used as the basis in order to develop an integrated waste management scheme for CEZ. The waste management classification revealed that the non-hazardous solid waste that can be recycled amounted to 729 cu.m covering a fraction of 51 percent of the total hazardous solid waste generation while the industrial waste that can be utilized as an alternative fuel or as supplementary fuel has a total volume of 893 cu.m. It makes up the 8 percent of the total industrial waste generation at the industrial estate site. The waste for energy recovery has an estimated energy content of approximately 18,200 kj/kg, which is equivalent to the energy of lignite coal. The energy content of the combustible solid waste is to be used as alternative fuel in cement kiln plants. The industrial solid waste that is to be biologically stabilized to recover compost amounted to 17 cu.m or a fraction of 1 percent of the total non-hazardous solid waste generation. On the hazardous waste, the total quantity of the hazardous waste that can be recycled is 4538 cu.m, which make up 50 percent of the total hazardous waste generation, It includes solvent, used oil, solder dross and lead acid battery as well as contaminated tin cans to be reused as containers for stabilized waste.The hazardous waste left for treatment has a total volume of 4297 cu.m or 47 percent of the total hazardous waste generation and the hazardous waste left for immediate disposal has a volume of 38 cu.m.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Integrated solid waste management -- Philippines -- Cavite; Hazardous wastes -- Philippines -- Cavite; Factory and trade waste -- Philippines -- Cavite; Refuse and refuse disposal -- Philippines -- Cavite; Recycling (Waste, etc.) -- Philippines -- Cavite